Efficacy of halosulfuron-methyl in the management of Navua sedge (Cyperus aromaticus): differential responses of plants with and without established rhizomes. (19th June 2022) - Chadha, Aakansha; Florentine, Singarayer K.; Dhileepan, Kunjithapatham; Turville, Christopher; Dowling, Kim
Abstract: Navua sedge is a creeping perennial sedge commonly found in tropical environments and is currently threatening many agroecosystems and ecosystems in Pacific Island countries and northern Queensland, Australia. Pasture and crop productions have been significantly impacted by this weed. The efficacy of halosulfuron-methyl on Navua sedge plants with and without well-established rhizomes was evaluated under glasshouse conditions. Halosulfuron-methyl was applied to plants with established rhizomes at three stages; mowed, pre-flowering, and flowering growth stages, whereas plants without established rhizomes were treated at seedling, pre-flowering and flowering growth stages. At each application time, halosulfuron-methyl was applied at four dose rates of 0, 38, 75, and 150 g ai ha −1 . Mortality of 27.5%, 0%, and 5% was recorded in rhizomatous Navua sedge when treated with 75 g ai ha −1 of halosulfuron-methyl at the mowed, pre-flowering stage and flowering stages, respectively. At 10 wk after treatment (WAT), there were no tillers in surviving plants treated at any of the application times. By 16 WAT, the number of tillers increased to 15, 24, and 26 in mowed, pre-flowering, and flowering stages, respectively. Although halosulfuron-methyl is effective in controlling aboveground growth, subsequent emergence of new growth from the rhizome confirms the failure of the herbicide to kill the rhizome. Application of 75 g ai ha −1 of halosulfuron-methyl provided 100% mortality in plants treated at seedling and pre-flowering stages, and 98% mortality when treated at flowering stage in non-rhizomatous plants. A single application of halosulfuron-methyl is highly effective at controlling Navua sedge seedlings but not effective at controlling plants with established rhizomes.